2010
DOI: 10.1155/2010/950201
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as Novel Biomarkers for Breast Cancer

Abstract: Breast cancer is a complex phenotypically diverse genetic disease, involving a variety of changes in gene expression and structure. Recent advances in molecular profiling technology have made great progress in unravelling the molecular taxonomy of breast cancer, which has shed new light on the aetiology of the disease and also heralded great potential for the development of novel biomarkers and therapeutic targets. Mi(cro)RNAs are a contemporary class of small noncoding endogenous RNA molecules, generating gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 54 publications
4
122
0
2
Order By: Relevance
“…Based on their binding affinity to hundreds of different mRNAs, they are involved in the regulation of various cellular processes (5 ). Because miR loci frequently map to fragile chromosomal regions harboring DNA amplifications, deletions, or translocations, their expression is often deregulated during tumorigenesis and contributes to tumor progression (6,7 ). MiRs are released into the blood circulation by apoptotic and necrotic cells (8 ) as well as by active secretion in small particles, such as exosomes.…”
Section: © 2013 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Based on their binding affinity to hundreds of different mRNAs, they are involved in the regulation of various cellular processes (5 ). Because miR loci frequently map to fragile chromosomal regions harboring DNA amplifications, deletions, or translocations, their expression is often deregulated during tumorigenesis and contributes to tumor progression (6,7 ). MiRs are released into the blood circulation by apoptotic and necrotic cells (8 ) as well as by active secretion in small particles, such as exosomes.…”
Section: © 2013 American Association For Clinical Chemistrymentioning
confidence: 99%
“…36 Alternatively, studies have demonstrated that lack of microRNA production can permit uncontrolled cellular proliferation in the setting of leukemia 37 and breast cancer. 38 Recently, Roggli et al 39 demonstrated in a mouse diabetic model that inflammatory cytokines elicit production of microRNA species that may be involved in the development of pancreatic ␤-cell failure, whereas the direct connection between increased production of microRNA targeting collagen gene expression and diabetes is still unclear. This pathophysiology can certainly explain our findings, but of course, more investigation is necessary of to further evaluate the role microRNA species play in the development of diabetes.…”
Section: Figure 8 Amentioning
confidence: 99%
“…As with many cancers, progress in early breast cancer detection has been inadequate (4 ), and methods for determining diagnosis and prognosis of breast cancer are still limited to invasive procedures, such as tissue biopsies for histological examination (5,6 ). Advances in understanding the cancer cell at the molecular level have enabled development of several targeted therapies that have advanced the treatment of relevant patient subgroups.…”
mentioning
confidence: 99%